Spam Draining using Composite Boyer Moore Algorithm and Stemming - Rajesh Kumar Maurya, Rishabh, Vinod Kumar, Dharmendra Kumar Roy (International Journal of Advanced Science and Technology, 2020)
The main motive behind the concept of email was to find quicker and well organized way for information transfer. Due to its speed, it gained global acceptance very quickly. But some tried to use its acceptance for their forgery and fraudulent activities. Those mails are categorized as spam. Spams not only occupy memory but also waste time, due to which it was very important to spot spam from mails. Various methods were developed in order to detect spam. The objective of this paper is to study the work done in the field of spam recognition and present a method involving Composite Boyer Moore, Graylist filter, Nave Bayes algorithm and Stemming. A comparative study along with Boyer Moore algorithm performed.